2004
DOI: 10.1023/b:maci.0000037649.24025.2c
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns and Maternal Well-Being in Postpartum Women

Abstract: In this group of women, subjects with older infants or no other children reported higher HC and lower O prepregnancy to postpartum. Postpartum SE, education, and socioeconomic status were predictors of maternal well-being. In general, better maternal well-being was found among subjects maintaining or increasing SE compared to no SE or decreased SE prepregnancy to postpartum. Support from partner/husband, family, and friends were significant factors in maintaining or increasing SE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 19 publications
3
67
2
1
Order By: Relevance
“…Some report that MVPA decreases before and after the birth of a child (Brown et al 2009;Pereira et al 2007) with a slight rebound postpartum (Pereira et al 2007), whereas others report no difference in MVPA between parents and non-parents and for individuals who move into parenthood (Blum et al 2004;Treuth et al 2005). Most of these studies use cross-sectional or short-span longitudinal data, and so fail to examine long-term dynamics in MVPA across the transition to parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…Some report that MVPA decreases before and after the birth of a child (Brown et al 2009;Pereira et al 2007) with a slight rebound postpartum (Pereira et al 2007), whereas others report no difference in MVPA between parents and non-parents and for individuals who move into parenthood (Blum et al 2004;Treuth et al 2005). Most of these studies use cross-sectional or short-span longitudinal data, and so fail to examine long-term dynamics in MVPA across the transition to parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…37 Additionally, some epidemiological studies have reported the inverse relationship between prenatal physical activity and maternal postpartum depression. 38,39 The maternalfetal benefits in maternal physical activity have encouraged some institutions to promote the practice of physical exercises during pregnancy, establishing general guidelines that propose the gradual restart of postpartum routines. Despite such benefits, both pregnancy and postpartum are associated with lower levels of physical activity.…”
Section: Physical Activitymentioning
confidence: 99%
“…43 Despite these observations, many women do not follow such recommendations. 38 Some studies, including qualitative approaches suggest the existence of barriers such as maternity and family responsibilities, lack of time, lack of family and/or social support and fatigue among others. 45,46 The current evidence suggests that mothers who combine physical activity with changes in the dietary intake are most likely to return to their pre-pregnancy weight, but further researches should be done about the influence of breastfeeding and other factors that may intermediate this relationship, such as socioeconomic level.…”
Section: Physical Activitymentioning
confidence: 99%
“…The existing studies suggest that women with greater levels of prenatal physical activity and higher family income are more likely to be active during postpartum [ 30 ]. Blum et al [ 38 ] administered the Kaiser Physical Activity Survey (KPAS) to 91 postpartum women in Maine and found that women with older infants reported greater increases in household/childcare physical activity and lower occupational physical activity from prepregnancy to postpartum as compared to women with younger infants. In general, women who maintained or increased activity and/or sports participation from prepregnancy to postpartum had better overall maternal well-being and significantly better perception of partner's/ husband's participation in childcare and support for maternal role from family and friends, compared to women reporting no or decreased activity participation.…”
Section: Determinants Of Physical Activity In Postpartummentioning
confidence: 99%
“…A second study which randomized overweight women to an exercise program and a structured diet found that the intervention arm successfully lost weight and most maintained weight loss by 1 year after delivery [ 89 ]. However, support from professionals and family is crucial for women to engage in physical activity during the postpartum period [ 38 ].Weight loss interventions which begin during pregnancy [ 90 , 91 ] may be more effective than those initiated only in the postpartum period [ 89 , 92 , 93 ] given the strong association between GWG and postpartum weight retention and the fact that it may be difficult to reduce postpartum weight retention without first preventing excessive GWG during pregnancy [ 94 ].It remains unclear whether clinically relevant postpartum weight loss can be achieved in obese and overweight postpartum women and what form of physical activity intervention would be optimal. The Active Mothers Postpartum (AMP) trial enrolled a total of 450 overweight or obese women at 6 weeks postpartum [ 93 ].…”
mentioning
confidence: 99%